2021
DOI: 10.1051/cagri/2021027
|View full text |Cite
|
Sign up to set email alerts
|

The plight of female agricultural wageworkers in Morocco during the COVID-19 pandemic

Abstract: While vaccination campaigns against COVID-19 were launched worldwide, a drama has been unfolding in the Moroccan countryside. It has been marked, over the last couple of decades, by rapid agrarian transformation, manifestations of which have included expanding irrigation frontiers and the increasing growth of high-value crops. These dynamics rely strongly on female agricultural wageworkers. Although they earn low wages, their income is crucial and is used to care for loved ones by paying for school fees, rent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…The results of other studies also found that farmers experienced many challenges due to the COVID-19 pandemic and did not get optimal support from the government (Nchanjia & Lutomia, 2021;Wegerif, 2021). Five studies (Bossenbroek & Ftouhi, 2021;Jaacks et al, 2021;Kulkarni et al, 2021;Landry et al, 2021;Lusk & Chandra, 2021) described about farmers on their social life from the production process (inputs, harvest and sell), accessing incentives, finding workers and lower income with high risk of disease. All study highlighted the farmers' difficulties in cultivating the land to selling the crops.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of other studies also found that farmers experienced many challenges due to the COVID-19 pandemic and did not get optimal support from the government (Nchanjia & Lutomia, 2021;Wegerif, 2021). Five studies (Bossenbroek & Ftouhi, 2021;Jaacks et al, 2021;Kulkarni et al, 2021;Landry et al, 2021;Lusk & Chandra, 2021) described about farmers on their social life from the production process (inputs, harvest and sell), accessing incentives, finding workers and lower income with high risk of disease. All study highlighted the farmers' difficulties in cultivating the land to selling the crops.…”
Section: Discussionmentioning
confidence: 99%
“…This review found that six articles (Bossenbroek & Ftouhi, 2021;Cevher et al, 2021;Fang et al, 2021;Landry et al, 2021;Quandt et al, 2021;Shafi et al, 2021) described the effect of pandemic on mental health in farmers such as anxiety, fear, worry, depression, stress and substance use disorders. Psychological problems during COVID-19 can be directed by the impact of the disease, restriction that lead to limited access to social support facilities and uncertainty and stress resulting from loss jobs and livelihoods (Semo & Frissa, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women's participation in farming activities is increasing in Morocco, but rural women still face poorer education and more limited access to economic opportunities than men (Boutkhil, 2019). Furthermore, they often work without a contract or social security coverage (Bossenbroek & Ftouhi, 2021). The lack of social security and access to land for women is deeply rooted in national factors (Gough et al, 2004; Thompson‐Hall et al, 2016), including the land inheritance system (Price‐Smith, 2001; Saad‐Zoy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%